The Role of Good Corporate Governance in Profit Management - Rahayu, Rika Meidiana; Permatasari, Maridha Chintia (Politeknik Negeri Madiun, 2025)
Profit management is the manipulation of transactions within the financial statement based on certain decisions by managers. This can mislead stakeholders who want to know the company's economic performance. Companies need to their economic performance in the long term and minimize profit management through a good corporate governance system in order to control, manage, and supervise the company's operational mechanisms. This study aims to identify the role of Good Corporate Governance on profit management. Data collection followed the procedure of library research. The results of the analysis showed that Good Corporate Governance played a role in profit management by providing supervision by a permanent audit committee for a period. Supervision of management could reduce profit management practices and agency theory for profit management.